Music from the Perspective of Salaf and Khalaf Scholars - Falihah Lailatus Sa’adah; Nabila Aulia Risyad Yusmardhani; Zahra Fauziyah (al-Afkar, Journal For Islamic Studies, 2026)
Music is a common practice in our country for conveying Islamic messages. Preaching through music is readily accepted by the majority of the general public. However, as Muslims, we must heed the rules and regulations surrounding music. Within the legal context of music, there are differing views on music: those that consider it haram (forbidden) and those that permit it under certain conditions. In the differing opinions of scholars, the original meaning does not imply conflict or disagreement. However, human nature, which then causes differences among scholars, eventually leads to disagreements and escalates into conflict. This is because their hearts are too narrow to accept the reality of differences. Differences of opinion are not inherently synonymous with hostility and hatred. They can occur without diminishing respect and appreciation.